2003
DOI: 10.1063/1.1558038
|View full text |Cite
|
Sign up to set email alerts
|

Nanoadhesion of elastic bodies: Roughness and temperature effects

Abstract: We present a simple model which illustrates the nature of the contact between an elastic solid and a hard surface with cosine-corrugation profile. In the continuum limit, the contact mechanics depends only on two dimensionless parameters, namely the ratio between the height and wavelength of the substrate corrugation, and the ratio between a surface energy and an elastic energy. The theory shows that the complete contact state is always a local energy minima ͑in the zero temperature limit͒, but for large enoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…We have confirmed our results with the total energy calculated by Zilberman and Persson's equation [4] and the equilibrium condition calculated by Johnson's equation [2]. It is shown that our results conform to those of Zilberman and In Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We have confirmed our results with the total energy calculated by Zilberman and Persson's equation [4] and the equilibrium condition calculated by Johnson's equation [2]. It is shown that our results conform to those of Zilberman and In Fig.…”
Section: Resultssupporting
confidence: 91%
“…In the case of a rigid body in contact with an elastic body, the elastic modulus, * E is given by The net surface displacement on the elastic body within the contact region is given by [3], [4]…”
Section: Pressure Distribution and Displacement On The Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…57) An important factor influencing the measurement of adhesive force is the surface roughness, as discussed in the previous theoretical and experimental works. [150][151][152][153][154][155] When two rough surfaces are brought into contact, the real contact can happen only on the protruding points of the interface. That is, the real area of contact can be decreased as a result of surface roughness, which subsequently decreases the adhesive force.…”
Section: Adhesion Forcementioning
confidence: 99%